2005
DOI: 10.1142/s0218810405002577
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Metacarpal Synostosis Treated by Double Bone Blocks Technique: A Case Report From Thailand

Abstract: Congenital metacarpal synostosis is a rare congenital anomaly in the hand, especially in our area. There were several reports of surgical techniques for correction deformities. We report this rare condition in our hospital and treatment with the metacarpal osteotomy and double bone blocks technique of grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…One unique element of the current case presentation is the age of the patient and his proximity to full skeletal maturity. There is limited data in the literature regarding surgical treatment of metacarpal synostosis in skeletally mature patients; our review identified only three documented cases of patients older than age 15 [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One unique element of the current case presentation is the age of the patient and his proximity to full skeletal maturity. There is limited data in the literature regarding surgical treatment of metacarpal synostosis in skeletally mature patients; our review identified only three documented cases of patients older than age 15 [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly, Kirschner-wire (K-wire) fixation, tendon transposition, and Hoffman lengtheners were utilized ( Table 2 ; Figure 5 ). One report in 2005 described the use of two osteotomies: one oblique-transverse and another vertical osteotomy with the placement of two bone blocks [ 8 ]. In 1997, Kawabata et al.…”
Section: Discussionmentioning
confidence: 99%
“…Konkaen University reported the treatment of congenital metacarpal synostosis with bone blocked. 36 Pobe Luangjarmekorn reported single-stage radialization and pollicization for the radial longitudinal deficiency with thumb hypoplasia. 37 • For the Private Hospital section, Wichit Siritatamrong and his team set up the microsurgery team at Chularat 3 Hospital, which is now famous for the treatment of traumatic hand injury (►Fig.…”
Section: • For Congenital Hand Anomaly Surut Jianmongkol Formmentioning
confidence: 99%
“…Коррекция укорочения пястных костей производится разными способами: применяется остеотомия в сочетании с одномоментным удлинением пястных костей [2,3,8,10,19]; описаны варианты удлинения пястных костей при помощи различных дистракционных аппаратов [9,12,16]. Однако степень укорочения, при котором эти операции показаны, четко не определена.…”
Section: Introductionunclassified